Effect of a Weight Loss Program on Body Composition and Metabolic Syndrome Markers in Obese Weight Cyclers - Samuel Oetoro; Lukman H Makmun; Widjaja Lukito; Andi Wijaya (Acta Medica Indonesiana, 2016)
Aim: to evaluate the effect of weight loss program on fat mass, visceral fat rating and metabolic syndrome markers in obese subjects with weight cycling. Methods: this was an 8-week open trial. The subjects were recruited consecutively from Balai Kota DKI Jaya. Subjects were classified into two groups according to the fluctuation of weight gain (weight cycling/WC and first encounter obesity/FEO group). Both groups were assigned to receive weight loss program consisted with following goals: a 1000 kcal energy intake reduction and 45 minutes mild-to-moderate intensity physical activity three times a week. Body composition (fat mass, visceral fat rating), and metabolic syndrome markers (waist circumference and triglyceride levels) were measured at baseline, week 4 and at the end of study. Results: seventy two subjects completed the study (34 subjects in WC group and 38 subjects in FEO group). Following weight loss program, a decrease in fat mass, visceral fat rating, and waist circumference was lower in WC group compared with FEO group but it was not statistically significant (p>0.05). Triglyceride levels were decreased in the FEO group while it was increased in WC group. However the difference was not significant (p=0.055). Conclusion: weight loss program may contribute to changes in body composition and metabolic syndrome markers in obese subjects, which the response appears to be worse in weight cyclers.